PERCEPTIONS OF UNIMAS STUDENTS ON PORNOGRAPHY ADDICTION - Norfarhana, Ambran (Universiti Malaysia Sarawak (UNIMAS), 2021)
Pornography is considered a taboo topic in Malaysia. This research explores the perception of pornography addiction among UNIMAS students on their general opinions toward pornography addiction, their insights on the effects of pornography addiction on an individual’s well-being, and their perspectives on the cross-cultural issues of religious views on pornography addiction. As well as discovering students’ opinions on the initiative to prevent pornography addiction in Malaysia. Eight participants asked were interviewed with a semistructured questionnaire in the face-to-face interview. Data collected in this study were voice recorded, transcribed, and then using Thematic Analysis by Braun & Clarke’s phases of analysis. The finding revealed that UNIMAS students from the Faculty of Cognitive Sciences and Human Development know what pornography addiction is. They can distinguish the effects of pornography addiction on individual well-being. The participants also reported on the cross-cultural differences in pornography addiction issues and also shared their religious views regarding pornography addiction. The suggestions and recommendations on how we can avoid or prevent pornography addiction among students were also discussed